2021
DOI: 10.3389/fphar.2021.654808
|View full text |Cite
|
Sign up to set email alerts
|

Unconjugated Bilirubin Attenuates DSS-Induced Colitis Potentially via Enhancement of Bilirubin Reabsorption

Abstract: Studies increasingly show that ulcerative colitis (UC) is a consequence of an imbalance between oxidative stress and antioxidant capacity. Bilirubin exerts an anti-inflammatory effect by scavenging reactive oxygen species (ROS), although the exact mechanism is not completely understood. The aim of this study was to determine the role of serum bilirubin in UC using patient data and a mouse model of dextran sodium sulfate (DSS)-induced colitis. We found that low levels of serum bilirubin correlated to a higher r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…IBIL is a powerful antioxidant, and the work by Zhao et al [23] demonstrated that IBIL can directly scavenge superoxide anion radicals at the sites of inflammation. Furthermore, in a mouse model of autoimmune arthritis, exogenous IBIL injections significantly reduced oxidative DNA damage, neutrophil infiltration, and fibrin deposition in the joint cavity, leading to a decrease in inflammation and alleviating the symptoms of joint damage [24].…”
Section: Discussionmentioning
confidence: 99%
“…IBIL is a powerful antioxidant, and the work by Zhao et al [23] demonstrated that IBIL can directly scavenge superoxide anion radicals at the sites of inflammation. Furthermore, in a mouse model of autoimmune arthritis, exogenous IBIL injections significantly reduced oxidative DNA damage, neutrophil infiltration, and fibrin deposition in the joint cavity, leading to a decrease in inflammation and alleviating the symptoms of joint damage [24].…”
Section: Discussionmentioning
confidence: 99%
“…IBIL is a powerful antioxidant, and the work by Zhao et al [23] demonstrated that IBIL can directly scavenge superoxide anion radicals at the sites of in ammation. Furthermore, in a mouse model of autoimmune arthritis, exogenous IBIL injections signi cantly reduced oxidative DNA damage, neutrophil in ltration, and brin deposition in the joint cavity, leading to a decrease in in ammation and alleviating the symptoms of joint damage [24].…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigations have demonstrated a variety of biological properties of this the metabolite of iron porphyrin at physiological concentrations, such as anti-oxidative and antiinflammatory (39,40). In animal models of experimental colitis, BIL protects mice from DSS-induced colitis, possibly via reducing mucosal leukocyte infiltration, maintaining redox homeostasis (41), and promoting BIL reabsorption via enterohepatic cycling (42). With regard to human IBD, patients with the Gilbert's polymorphism have a decreased risk of CD (43) and patients with IBD show significantly lower levels of BIL than controls (20).…”
Section: Discussionmentioning
confidence: 99%